2018
DOI: 10.4269/ajtmh.17-0917
|View full text |Cite
|
Sign up to set email alerts
|

Serotype Distribution and Antimicrobial Resistance of Shigella Species in Bangui, Central African Republic, from 2002 to 2013

Abstract: is a major cause of severe diarrhea in children less than the age of 5 years in sub-Saharan Africa. The aim of this study was to describe the (sub-)serotype distribution and antimicrobial susceptibility of serogroups from Centrafrican patients with diarrhea between 2002 and 2013. We collected 443 isolates in total. The most common serogroups were ( = 243, 54.9%), followed by ( = 90, 20.3%) and ( = 72, 16.3%). The high diversity of (sub-)serotypes of and may impede the development of an efficient vaccine. Rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
(24 reference statements)
1
11
1
Order By: Relevance
“…ree Shigella serogroups, serogroup A (Shigella dysenteriae type 1), B (S. flexneri), and C (S. sonnei), caused bacillary dysentery among children under five years at Banadir Hospital, Somalia. Serogroup D (Shigella boydii) was absent, an unsurprising finding since this bacterium is more prevalent in Southeast Asia (Nepal and Bangladesh) Canadian Journal of Infectious Diseases and Medical Microbiology [17] but rarely reported elsewhere in the Central African Republic [18], Ethiopia, and Egypt [19]. In our study, the most prevalent serogroup was Shigella flexneri (70%), a finding consistent with other reports from Nigeria [20], Central Africa Republic [18], Nepal [21], Iran, India, and Eritrea [22,23]-(4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ree Shigella serogroups, serogroup A (Shigella dysenteriae type 1), B (S. flexneri), and C (S. sonnei), caused bacillary dysentery among children under five years at Banadir Hospital, Somalia. Serogroup D (Shigella boydii) was absent, an unsurprising finding since this bacterium is more prevalent in Southeast Asia (Nepal and Bangladesh) Canadian Journal of Infectious Diseases and Medical Microbiology [17] but rarely reported elsewhere in the Central African Republic [18], Ethiopia, and Egypt [19]. In our study, the most prevalent serogroup was Shigella flexneri (70%), a finding consistent with other reports from Nigeria [20], Central Africa Republic [18], Nepal [21], Iran, India, and Eritrea [22,23]-(4).…”
Section: Discussionmentioning
confidence: 99%
“…Serogroup D (Shigella boydii) was absent, an unsurprising finding since this bacterium is more prevalent in Southeast Asia (Nepal and Bangladesh) Canadian Journal of Infectious Diseases and Medical Microbiology [17] but rarely reported elsewhere in the Central African Republic [18], Ethiopia, and Egypt [19]. In our study, the most prevalent serogroup was Shigella flexneri (70%), a finding consistent with other reports from Nigeria [20], Central Africa Republic [18], Nepal [21], Iran, India, and Eritrea [22,23]-(4). Epidemiologically, Shigella serogroups show geographical stratification based on the economic and development status of a country, as well as the virulence of a given serogroup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies [23,34,36,37,57] were found in our search. Two-thirds reported on outbreak investigations, and Shigella dysenteriae type 1 was the predominant serotype.…”
Section: Shigella Spp Resistancementioning
confidence: 99%
“…Many reproductive health needs of the population are not met as there is only 0.3 nurses/midwives per 1000 population and only 40% of births are attended by skilled healthcare personnel [ 12 ]. Data on microbiology and ABR in the CAR are sporadic, with most data focusing on the ABR of the Enterobacteriaceae, and are rarely specific to the paediatric population [ 13 – 17 ]. To our knowledge, no studies have been published on neonatal infections and their ABR in CAR.…”
Section: Introductionmentioning
confidence: 99%